Diversity and Habitat Characteristics of Tropical Pitcher Plant (Nepenthes sp.) in the Harau Valley Nature Reserve Area Lima Puluh Kota Regency - Nurhaliza; Yoza, Defri; Pebriandi (Journal of Tropical Silviculture, 2024)
Nepenthes is a unique carnivorous plant, both in terms of shape, color and how to get food. The purpose of this study was to determine the diversity of Nepenthes species and determine how the characteristics of Nepenthes habitat in the Harau Valley Nature Reserve. This research has been conducted in December 2023 in Harau Valley Nature Reserve. The method used in the research was direct observation method with purposive sampling technique by making 20x20 meter plot in natural forest, and 2x2 meter plot in shrubs. The parameters observed were the number of Nepenthes found in each plot, temperature, air humidity, soil pH and light intensity. After identifying the species, 3 species of Nepenthes were found, namely Nepenthes albomarginata, Nepenthes eustachya, and Nepenthes gracilis with a total of 160 individuals. For the results of measurements of physical environmental factors in natural forests, the average temperature was 24.70°C, humidity 83.90%, soil pH 5.60 and light intensity 2882 lux, while in shrubs the average temperature was 27.90°C, humidity 74.3%, soil pH 5.20 and light intensity 3679 lux. Keywords: Diversity, habitat characteristics, harau valley nature reserve, Nepenthes